The rise of online advertising and its impact on the future of Philippine newspapers - Concha, Jean Louise Villanueva (2012)
"In this study, the future of print newspapers was seen as a function of the financial aspects in its production: advertising and circulation. With the growth of digital media in advanced countries and the decline in newspaper readership, many newspapers have ceased to exist as printed products and evolved to an online information source. This phenomenon was localized but included only the country's major national broadsheets. By interviewing experts from broadsheets and advertising agencies, and surveying Metro Manila residents about their news and advertisement viewing habits, the researchers found that newspaper remains to be a highly preferred news and advertisement medium across birth cohorts. Though readership has declined compared to previous decades, newspaper revenues are still sufficient for the maintenance of print operations. The online media, on the other hand, has a very small base compared to other countries yet is continually on the rise. The broadsheets view this is as an opportunity rather than a threat, and have ventured into the online world to extend the bastion of quality journalism. Print production of broadsheets in country thus remains in the traditional media, and measures to encourage younger age groups to read newspapers have been started to sustain the printed page."